Dicyclomine Hydrochloride Malpractice Leads to Amputation and Multidisciplinary Team Approach Brings Normal Life - Sudhir Ramkishore Mishra; Snigdha Mishra (Journal of Surgical Specialties and Rural Practice, 2024)
Dicyclomine hydrochloride is a common drug used for abdominal pain; sometimes, its inadvertent use can lead to disastrous situation. This case report highlights how the inadvertent use of dicyclomine hydrochloride led to upper limb amputation and how a multidisciplinary team helped her to live a near-normal life.